2009
DOI: 10.1097/01.hp.0000348459.02616.41
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Contamination during Removal of Radioactive Seeds from Surgically Excised Tissue

Abstract: The purpose of this study was to determine whether the use of a scalpel or electrocautery to remove radioactive sealed sources ("seeds") from surgically excised tissue could damage the seed and cause it to leak its radioactive contents. Attempts were made to cut or burn Oncura Model 6711 non-radioactive seeds while in pig muscle or on a stainless steel plate. Additionally, one active 125I seed was purposely charred using pressure with an electrocautery knife to see whether the casing could be damaged. Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Any loss requiring follow up would be documented in the patient medical record, including an absorbed dose estimate. Breached or leaking seeds were not expected using typical surgical procedures (Classic et al 2009); however, in the rare event of unexpected seed leakage, Radiation Safety would be contacted to conduct a radioactive contamination assessment. If leakage were confirmed, all contaminated materials would be handled as radioactive waste.…”
Section: Emergency Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Any loss requiring follow up would be documented in the patient medical record, including an absorbed dose estimate. Breached or leaking seeds were not expected using typical surgical procedures (Classic et al 2009); however, in the rare event of unexpected seed leakage, Radiation Safety would be contacted to conduct a radioactive contamination assessment. If leakage were confirmed, all contaminated materials would be handled as radioactive waste.…”
Section: Emergency Proceduresmentioning
confidence: 99%
“…A final radiation survey of the remaining specimen material was performed using the RSL gamma probe to verify the absence of any remaining implants. This important step was emphasized during training of the pathology staff to preclude the possibility of cutting of the seeds during microtome sectioning of specimens (Classic et al 2009). …”
Section: Specimen Handling In Pathologymentioning
confidence: 99%
“…The likelihood is minimal as the titanium seed shell is resistant to damage from the blades and forceps used in routine pathology practice. 13 This scenario is best to avoid and therefore our recommendation, and the recommendation of others, 14 is that snips or scissors should not be used in seed handling and that forceps should be only be used with finesse. 13,14 In studies specifically examining seed damage, complete seed severance has only been achieved by deliberately cutting a seed on a hard metal surface and by tightly grasping a seed with forceps.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 In studies specifically examining seed damage, complete seed severance has only been achieved by deliberately cutting a seed on a hard metal surface and by tightly grasping a seed with forceps. The likelihood is minimal as the titanium seed shell is resistant to damage from the blades and forceps used in routine pathology practice.…”
Section: Discussionmentioning
confidence: 99%
“…A study in pig tissue demonstrated that the I-125 seed had to be immobilized with tweezers before it could be damaged with either a scalpel or an electrocautery blade (Classic, Brunette, & Carlson, 2009). …”
Section: Discussionmentioning
confidence: 99%